Magnesium Attenuates Phosphate-Induced Deregulation of a MicroRNA Signature and Prevents Modulation of Smad1 and Osterix during the Course of Vascular Calcification. (22nd June 2016) - Louvet, Loïc; Metzinger, Laurent; Büchel, Janine; Steppan, Sonja; Massy, Ziad A.
Abstract : Vascular calcification (VC) is prevalent in patients suffering from chronic kidney disease (CKD). High phosphate levels promote VC by inducing abnormalities in mineral and bone metabolism. Previously, we demonstrated that magnesium (Mg 2+ ) prevents inorganic phosphate- (Pi-) induced VC in human aortic vascular smooth muscle cells (HAVSMC). As microRNAs (miR) modulate gene expression, we investigated the role of miR-29b, -30b, -125b, -133a, -143, and -204 in the protective effect of Mg 2+ on VC. HAVSMC were cultured in the presence of 3 mM Pi with or without 2 mM Mg 2+ chloride. Total RNA was extracted after 4 h, 24 h, day 3, day 7, and day 10. miR-30b, -133a, and -143 were downregulated during the time course of Pi-induced VC, whereas the addition of Mg 2+ restored (miR-30b) or improved (miR-133a, miR-143) their expression. The expression of specific targets Smad1 and Osterix was significantly increased in the presence of Pi and restored by coincubation with Mg 2+ . As miR-30b, miR-133a, and miR-143 are negatively regulated by Pi and restored by Mg 2+ with a congruent modulation of their known targets Runx2, Smad1, and Osterix, our results provide a potential mechanistic explanation of the observed upregulation of these master switches of osteogenesis during the course of VC.